Implications of climate change damage for agriculture: sectoral evidence from Pakistan - Ahmed, A.; Devadason, E.S.; Al-Amin, A.Q. (Springer Verlag (Germany), 2016)
This paper gives a projection of the possible damage of climate change on the agriculture sector of Pakistan for the period 2012–2037, based on a dynamic approach, using an environment-related applied computable general equilibrium model (CGE). Climate damage projections depict an upward trend for the period of review and are found to be higher than the global average. Further, the damage to the agricultural sector exceeds that for the overall economy. By sector, climatic damage disproportionately affects the major and minor crops, livestock and fisheries. The largest losses following climate change, relative to the other agricultural sectors, are expected for livestock. The reason for this is the orthodox system of production for livestock, with a low adaptability to negative shocks of climate change. Overall, the findings reveal the high exposure of the agriculture sector to climate damage. In this regard, policymakers in Pakistan should take seriously the effects of climate change on agriculture and consider suitable technology to mitigate those damages.